Deficiency of inactive rhomboid protein 2 (iRhom2) attenuates diet-induced hyperlipidaemia and early atherogenesis. Issue 1 (12th February 2021) - Hannemann, Carmen; Schecker, Johannes H; Brettschneider, Alica; Grune, Jana; Rösener, Nicole; Weller, Andrea; Stangl, Verena; Fisher, Edward A; Stangl, Karl; Ludwig, Antje; Hewing, Bernd
Abstract: Aims: Atherosclerosis is a chronic inflammatory disease of the arterial vessel wall and anti-inflammatory treatment strategies are currently pursued to lower cardiovascular disease burden. Modulation of recently discovered inactive rhomboid protein 2 (iRhom2) attenuates shedding of tumour necrosis factor-alpha (TNF-α) selectively from immune cells. The present study aims at investigating the impact of iRhom2 deficiency on the development of atherosclerosis. Methods and results: Low-density lipoprotein receptor (LDLR)-deficient mice with additional deficiency of iRhom2 (LDLR −/− iRhom2 −/− ) and control (LDLR −/− ) mice were fed a Western-type diet (WD) for 8 or 20 weeks to induce early or advanced atherosclerosis. Deficiency of iRhom2 resulted in a significant decrease in the size of early atherosclerotic plaques as determined in aortic root cross-sections. LDLR −/− iRhom2 −/− mice exhibited significantly lower serum levels of TNF-α and lower circulating and hepatic levels of cholesterol and triglycerides compared to LDLR −/− mice at 8 weeks of WD. Analyses of hepatic bile acid concentration and gene expression at 8 weeks of WD revealed that iRhom2 deficiency prevented WD-induced repression of hepatic bile acid synthesis in LDLR −/− mice. In contrast, at 20 weeks of WD, plaque size, plaque composition, and serum levels of TNF-α or cholesterol were not different between genotypes. Conclusion: Modulation of inflammation by iRhom2 deficiency attenuated diet-induced hyperlipidaemia and early atherogenesis in LDLR −/− mice. iRhom2 deficiency did not affect diet-induced plaque burden and composition in advanced atherosclerosis in LDLR −/− mice. Graphical Abstract: